USO DE UM SISTEMA DE INFORMAÇÃO GEOGRÁFICO COMO ELEMENTO DE GESTÃO AMBIENTAL EM UNIDADES DE CONSERVAÇÃO - Calheiros, Daniel Pinheiro (2005)
This paper uses a case study carried out in the Parque Estadual da Pedra Branca , and it is based on the geoprocessing results analysis. Technical competence on geoprocessing (a GIS tool), concepts related to preservation of natural resources and environmental management have been applied. Information has been inserted in a digital data-base (the data may be in different kind: either in figures, or in nouns, alphanumeric, visual or audio), and it has been possible to geoprocess them. Then analyses have been carried out and environmental classes have been created using the ArcGis software to comprehend the images gotten by the satellite Ikonos (100cm. x 100cm. pixel resolution). Thus, efficiently and with a low cost, digital, geo referred and up-to-date comprehension of the environment could be made, making easy access to more precise and often updating information. A movie in 3D has been prepared using a digital data-base in .mpg with 100 megabytes explaining the comprehension herein. This paper also argues that when a Rescue Plan of any Preserve Unit (PU) is made, it is recommended the use of a Geographic Information System (GIS). This system (GIS) reduces time and increases efficiency of making decisions, for instance, which class and category the unit will be part of. It may also help define what preventing and mitigating measures should be taken for the effective preservation of the ecosystem.